PENGARUH LATIHAN ABDOMINAL TERHADAP KEMAMPUAN HEADING PEMAIN SEPAK BOLA U 19-21 GUNUNG MEDAN DHARMASARAYA - Muhammad Rizki; Zuhar Ricky; Maldin Ahmad Burhan (Dharmas Journal of Sport, 2022)
This research was motivated by the lack of good heading skills of U 19-21 soccer players in gunung Medan, Dharmasaraya. Efforts to overcome these problems require abdominal exercises. This study aims to determine whether abdominal exercise has an effect on the heading ability of dharmasaraya mountain soccer players. This research is a type of quantitative research using an experimental method approach. While the form of research design used is "one-group pretest-posttest design". The population of this study were all soccer players U 19-21 Gunung Medan dharmasaraya, totaling 16 people. The sample of this research is the dharmasaraya mountain soccer player. The data collection technique used in this study was a heading ability test. The data analysis technique used in this research is normality test and hypothesis testing through SPSS 20 at 0.06 level. The results showed that abdominal exercise had a good influence on the results of the heading ability of U 19-21 soccer players in Gunung Medan Dharmasaraya to learn, this can be seen from the acquisition of the average pretest and posttest scores obtained from U19 soccer players. 21 Gunung Medan dharmasaraya with an average pretest of 5.6 and posttest of 7.48. Based on the analysis carried out, obtained a significant value of abdominal exercise.